Comparative analysis of fecal microbiota of central and eastern black-necked cranes (Grus nigricollis) wintering in Yunnan Province, China - Ruimei Wang; Yixuan Wang; Lulu Deng; Binghui Wang; Mingfei Shi; Zeya Yang; Dong Hu; Zijiao Zhao; Ruiling Yuan; Jiuxuan Zhou (PeerJ)
The black-necked crane (Grus nigricollis) is the sole crane species globally that inhabits, breeds, and flourishes in high plateau environments. There are many microbial communities in the gastrointestinal tract of birds, which play an important role in the health, nutrition, and physiology of birds. This study utilized high-throughput sequencing of the 16S rRNA gene to investigate and compare the core gut microbiota of black-necked cranes in two overwintering populations of Yunnan Province, China. A total of 34,297 operational taxonomic units were identified, belonging to 49 phyla, 130 classes, 276 orders, 365 families, and 775 genera. Alpha diversity analysis indicated significant differences in the diversity of gut microbial communities between the two wintering populations, with the central population exhibiting markedly higher diversity and richness compared to the eastern population. Principal coordinate analysis revealed a clear separation of the two populations of fecal samples, suggesting notable differences in microbial communities between the populations. The dominant phyla in the eastern population were Firmicutes, followed by Proteobacteria, whereas the central population was primarily dominated by Firmicutes, Proteobacteria, and Actinobacteria. At the genus level, Lactobacillus had the highest abundance in the intestinal microbiota of the two populations. Additionally, a variety of potential pathogenic bacteria was also found, including Enterococcus, Acinetobacter, Campylobacter, Escherichia-Shigella, and Streptococcus, which may pose a risk of transmission among local black-necked crane populations. Appropriate measures should be taken to protect the health of black-necked cranes and reduce the spread of diseases.